Green Hydrogen Synthesis from Human Urine as Sustainable Bioenergy Resources - Odili, Blossom; Igbafe, Sylvia; Yusuff, Adeyinka Sikiru; Adebomehin, Akeem Aderibigbe; Igbafe, Anselm Iuebego (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
With the earths cry for help as pollution rate increases, researchers are faced with a common task of tackling pollution resulting from dependence on fossil fuel as well as delivering sustainable energy. Renewable energy resources such as solar, wind, hydro to mention a few are currently finding applications within the world energy mix but some limitations which range from meteorology of locations to expected maximum energy output attainable. Hydrogen, the most abundant element in the world stand chance of abating this problem. However conventional method of its producing, poses severe treat to the atmospheric environment with the release of oxides of carbon hence, referred as blue hydrogen. Contrarily, green hydrogen from human urine stands a more sustainable and environmentally friendly energy resource. This study was aimed to empirically model the synthesis of green hydrogen from urea in human urine by an electrolytic process. The synthesized hydrogen was characterized on physiochemical properties of conductivity, turbidity, pH, specific gravity and colour, while the precursor urine characterized on gender, exposure duration and storage temperature. The synthesis process was modelled using Microsoft excel solver for the overall cell energy or polarization curve model, the Faraday’s efficiency model and gas purity model at electrolyte concentrations of 25 wt./wt., 30 wt./wt. and 35 wt./wt. of potassium oxide (buffer} to urea over a five-temperature interval range of 45 to 85 oC. Findings revealed that the gas produced was 99.88% hydrogen at the cathode. Also, hydrogen produced increased with increase in electrolyte concentration and moderate temperature with optimal conditions at 35 w/w electrolyte concentration and 65 oC. However, the minimum cell voltage was 2.06 V at 85 oC and 35 w/w electrolyte concentration. With an exception of the Faraday’s efficiency model at 30 wt./wt. electrolyte concentration across the system’s operating temperature range yielding an R2 value of 0.711, all the models yielded coefficient of determination values in the range of 0.96 and 0.99, indicating good fit for the alkaline urine electrolysis for green hydrogen synthesis from human urine.